Results of a Single Institution Experience with Dose-Escalated Chemoradiation for Locally Advanced Unresectable Non-Small Cell Lung Cancer - Bernard, Mark E.; Glaser, Scott M.; Gill, Beant S.; Beriwal, Sushil; Heron, Dwight E.; Luketich, James D.; Friedland, David M.; Socinski, Mark A.; Greenberger, Joel S. (Frontiers in Oncology, 2017)
Abstract: Background: We determined factors associated with morbidity and outcomes of a series of non-small cell lung cancer (NSCLC) patients treated with dose escalated chemoradiotherapy at the University of Pittsburgh Lung Cancer Program. Methods and Materials: The records of 170 stage III NSCLC patients treated with definitive intent were retrospectively reviewed. All patients received 4D-CT simulation scan and had respiratory gating if tumor movement exceeded 5 mm. Overall survival (OS), locoregional control (LRC), and freedom from distant metastasis (FFDM) were calculated using log rank and Cox regression analysis. Results: For the present series of patients, median follow-up was 36.6 months, median survival 27.4 months, and the 2- and 4-year (OS) was 56.0 and 30.7%, respectively. The 4-year local regional control (LRC) and freedom from distant metastases (FFDM) were 43.9% and 40.7%, respectively. No benefit was associated with irradiation doses above 66 Gy in overall survival (OS) (p=0.586), LRC (p=0.440), or FFDM (p=0.230). On univariate analysis, variables associated with worse survival included: clinical stage IIIB (p=0.037), PTV over 450 cc (p<0.001), heart V30 over 40% (p-0.048), and esophageal mean dose over 20% (p=0.024), V5 (p-0.015), and V60 (p-0.011). On multivariable analysis, PTV above 450 cc (52.2 vs. 25.3 months, p<0.001) and esophageal V60 > 20% (43.8 vs. 21.3 months, p-0.01) were associated with lower survival. Grade 2 or higher acute lung toxicity and esophagitis were detected in 9.5% and 59.7%, respectively of patients. Grade 2 or higher acute lung toxicity was reduced if lung V5 was < 65 (7.4% vs. 23.8%, p=0.03). Grade 2 or higher acute esophagitis was reduced if V60 < 20% (62% vs. 81.3%, p=0.018). The use of Intensity Modulated Radiation Therapy (IMRT) was more frequent in stage IIIB compared to stage IIIA patients (56.5% vs. 39.5%, p=0.048), and was associated with a higher lung V5 and V10. Conclusions: The outcomes of a program of dose escalated chemoradiotherapy for unresectable stage IIIA and IIB NSCLC patients were consistent with other studies and showed no benefit to radiation doses above 66 Gy. Furthermore, maintaining low esophageal V60 and lung V5 were associated with lower morbidity and mortality.